Two new species of the genus Tetracanthella (Collembola; Isotomidae) from China - Xie, Zhijing; Potapov, Mikhail; Sun, Xin (Zootaxa, 2019)
Two new species, T. dorsoduplex sp. nov. (Zhejiang province) and T. wui sp. nov. (Jilin Province) are described. The former species belongs to ’sylvatica’ group and differs from all species of the genus by presence of only one pair of macrochaetae on Th. II–Abd. II and specific position of lateral s-chaetae on Abd. IV. The latter species belongs to ’stebaevae’ group and differs from closely related species by chaetotaxy of dens (1/5) and abundant axial chaetotaxy of abdominal tergites.